Pengaruh Sertifikasi Halal Terhadap Keputusan Pembelian Produk Scarlett Pada Mahasiswa Febi UIN Fatmawati Sukarno Bengkulu - Hasanah, Uswatun; Sari, Mila Ratna (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
The purpose of this study was to determine the effect of Halal Certification on Purchase Decisions for scarlett products in FEBI Students of Islamic Economics Study Program Fatmawati Sukamo Bengkulu State Islamic University. The quantitative research method with data analysis was processed through the SPSS 22 program. The research sample was selected using a purposive sampling technique which obtained 100 respondents. The results showed Halal certification has a positive effect on the decision to purchase scarlett products with a significance value (sig) 0.013 <0.05 and a t-value of 2.528. In general, the Halal Certificationhas an influence on purchasing decisions of scarlett products for FEBI Students of Islamic Economics Study Program Fatmawati Sukamo State Islamic University Bengkulu.